Effectiveness of Diabetes Self Management Education on Lifestyle in Type 2 Diabetes Mellitus Patients: A Literature Review - Kurniawan Laia; Kezia Triana; Lani Watania; Heman Pailak (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes Self-Management Education (DSME) is an act of nursing that facilitates knowledge, skills, and abilities. The purpose of DSME is to change the lifestyle of diabetic patients, especially in controlling blood glucose levels. In 2021, the International Diabetes Federation noted that the global prevalence of diabetes reached 10% (537 million people). Objective to ascertain the effectiveness of diabetes self-management education (DSME) on type 2 DM patients’ lifestyle. Thematic analysis method, a simplified approach is the method used in this literature review. The articles used were obtained through searching articles form several databases such as Google Scholar, MEDLINE, and PUBMED, using the keywords